Effects of grazing management and levels of concentrate supplementation on parasite establishment in two genotypes of lambs infected with Haemonchus contortus - Simon P Ginting; K.R Pond; Subandriyo . (Jurnal Ilmu Ternak dan Veteriner, 1996)
The effects of grazing systems, levels of feed supplementation and genotypes of sheep on the establishment ofHaemonchus contortus were studied in 36 St . Croix x Sumatra crosses (HC) and 36 Sumatra (S) male lambs . The lambs were artificially infected with Haemonchus larvae (L3) at a rate of 3,000 L3 per animal and fed concentrate supplement at 0 .5% body weight (BW) or at 1 .6% BW. The animals grazed clean Brachiaria brizantha pastures . Lambs grazing GM1 (grazing system with a 6-week rotational cycle) had egg counts of 3,936 t 1 .525 at week 18, and 29% of the lambs had PCV ranging from 7 .8 to 14 .6% . Lambs in GM3 (grazing system with a 12-week grazing cycle) had egg counts of 6,714 t 2,075 at week 28, and 24%ofthe lambs had PCV ranging from 7 .9 to 13.3% At these periods, all lambs in both GMI and GM3 were dosed with anthelmintics to prevent the death of the animals . Although the overall mean egg counts (4,543 t 318) of lambs on GM2 (grazing system with a  1-week grazing and 6-week resting periods) were higher (P<0 .001) than on GMI (2,944 t 325) or on GM3 (2,159 t 418), it was achieved without dosing with anthelmintics, since only I 1%ofthe Iambs in GM2ever reached PCV values less than 15%. Lambs fed supplements at 1.6%BW had lower (P<0.001) egg counts and higher (P<0 .001) PCV and serum protein than lambson 0.5 %BW supplement group . Egg counts and PCV values were not different (P>0 .10) between HC and the S lambs when fed supplement at 0.5% BW, but on 1 .6% supplement BW group, the egg counts were lower (P<0.001) in HC. It is concluded that a one-week grazing and a six- week resting system was superior than grazing systems with a 6- or 12-week rotational cycle . Improving the nutritional status of lambs by increasing the level of supplement offered could depress the establishment of Haemonchus in the Iambs . The HC and S lambs showed similar response to supplements at 0 .5% BW, but at 1 .6% BW the HC responded better than the S.   Key words: Grazing management, Haemonchus contortus, feed supplement, sheep